Advanced electrospun nanomaterials for highly efficient electrocatalysis. Issue 11 (10th September 2019) - Lu, Xiaofeng; Li, Meixuan; Wang, Huiyuan; Wang, Ce
Abstract : We highlight the recent developments of electrospun nanomaterials with controlled morphology, composition and architecture for highly efficient electrocatalysis. Abstract : In recent years, electrospun nanomaterials have been regarded as efficient electrocatalysts for energy storage and conversion due to their large surface area, unique chemical structure, easily tunable composition, and excellent electron and mass transportation properties. In this review, we will discuss the recent progress regarding the electrochemical catalytic reactions based on advanced electrospun nanomaterials, including the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), oxygen reduction reaction (ORR), carbon dioxide reduction reaction (CO2 RR), nitrogen reduction reaction (NRR), and small molecule oxidation reaction. After a brief description of the electrospinning technique and electrospun nanomaterials, we will focus on the relationship among the morphology, composition, and architecture of the electrospun nanomaterial-based electrocatalysts and their electrocatalytic performance. In addition, the remaining challenges and perspectives for further advances have been addressed. With the fast development of the electrocatalytic energy conversion devices, the research on the advanced electrospun nanomaterials in this field is anticipated to be significantly attractive and exciting in the near future.